Comparing the efficacy of thyroglobulin and thyroglobulin/ thyroid-stimulating hormone ratio models in predicting a successful response to radioactive iodine therapy - Yanli Ju; Lihua Wang; Fang Cheng; Fengyan Huang; Xueyu Chen; Qingqing Song; Juan Xiao; Xiaolu Zhu; Hongying Jia (BMC Endocrine Disorders, 2023)
Abstract Background The thyroglobulin (Tg)/ thyroid-stimulating hormone (TSH) ratio has manifested to be a reliable marker for predicting prognosis in patients with differentiated thyroid carcinoma (DTC). The objective of this study was to compare the efficacy of Tg and Tg/TSH ratio models in predicting a successful response to radioactive iodine therapy. Methods One thousand six hundred forty-two DTC patients receiving 131I radiotherapy were finally enrolled in this retrospective study. The patients were divided into a training set (n = 973) and a validation set (n = 669) by the patient consultation time (July 2019). A receiver-operating characteristic curve was constructed for Tg and the Tg/TSH ratio to establish their cutoffs. Then, the variables were screened by univariate logistic regression and incorporated into logistic prediction models by stepwise regression, where Tg/TSH was excluded from model 1 and Tg was excluded from model 2. Results In 1642 enrolled DTC patients, the first 131I radiotherapy had an excellent response in 855 patients. The cut-offs for Tg level and Tg/TSH ratio were 3.40 ng/ mL [area under the curve (AUC): 0.789] and 36.03 ng/mIU (AUC: 0.788), respectively. In addition, the AUC of the model including Tg was higher than that of the model including Tg/TSH in both the training set (0.837 vs 0.833) and the testing set (0.854 vs 0.836). Conclusions Both Tg and Tg/TSH ratios could be considered predictors of the effects of the first 131I ablative therapy. However, the prediction model including Tg performed better than the model including Tg/TSH.